PEMANFAATAN BUAH PEDADA (Sonneratia caseolaris) SEBAGAI BAHAN BAKU PEMBUATAN TEMPE DAN ANALISIS PROKSIMAT SERTA SIFAT ORGANOLEPTIKNYA - Fatisa, Yuni; Pitasari, Dewi (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2016)
Pedada fruit (Sonneratia caseoiaris) potential as a food source because it contains high nutrient. In this study pedada fruit used as raw material for making tempe. Tempe is made by the fermentation time of 48 hours with 5 grams of tempe yeast and nutritional levels tested. The results showed the moisture content, ash content, fat content, protein content, and carbohydrate content are respectively 79,87% (8Nl max 65%); 1,76% (8Nl max 1,5%); 3,50% (8NI min 10%); 3,90% (8NI min 10%) and 10,96% (8Nl max 2,5%). Organoleptic test results it can be concluded that the panelists liked the tempe of pedada fruit with test scores for flavor, color, texture and scent are respectively 3,6; 3,4; 3,68; and 4,6. Flavor, color, texture and aroma the tempe of pedada fruit acceptable by the panelists.